Exploration of the ichthyofauna of the Celike River, Leuser Ecosystem Area, East Aceh Regency, Aceh Province - Adli Waliul; Ilham Zulfahmi; Furqan Maghfiriadi; Siti Maulizar; Badratun Nafis; Al julismi; Muhammad Dawami; Agung Setia Batubara; Firman M Nur; Suraiya Nazlia (Depik, 2025)
It is necessary to collect data on the species of fish that live in a body of water, one of which is by carrying out an inventory of fish species. The method used is purposive sampling in places that are thought to have lots of fish, are easy to reach and represent the river area. The research parameters in this activity are the level of diversity, level of uniformity, level of dominance, level of species richness, level of similarity, distribution pattern, relationship between length and weight and condition factors. The aim of this research is to provide real benefits in an effort to find out the potential of what species of fish are found in the Leuser Ecosystem, especially the Celike River. There are 13 species of fish found in the Celike River in the Leuser Conservation Area, East Aceh, belonging to 7 families with a total of 132 individuals. The diversity index value is classified as moderate with a value for station 1 of 1.26 and station 4 of 1.49. The highest uniformity index is at station 5 and station 3. The uniformity index value at these stations has the same index (E = stable 0.91). Stations 2, 3, 4, 5 and station 6 have the highest dominance index values in the high category (C=0.87-1.18).Keywords:IchtiofaunaCelike RiverLeuser EcosystemExploration